Model Pengelolaan Zakat, Infaq, dan Shodaqoh dalam Pembangunan Suatu Negara - Sonia Silastia; Salsabila Rahmadini; Nadya Artha Joecha Mayvea; Abdillah Abdillah; Yayat Suharyat (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study is to analyze the management of the Infak Shodaqoh Zakat Fund (ZIS) in the context of poverty and how the ZIS Fund is managed to improve the country's economy. This research method uses qualitative research design and conducts data collection techniques using literature review methods with secondary data from previous research and other available sources. On the other hand, technical data analysis is carried out by drawing conclusions. These results show that the management of ZIS funds in Indonesia is still not perfect. As a result, there are still many people living in poverty.